Pemberdayaan Umkm Melalui Pelatihan Digital Marketing Di Desa Sumber Rejeki Kecamatan Banjar Tengah - Sari Indrawati; Ahmad Fadhillah; Rina Kartika (PT. AHLAL PUBLISHER NUSANTARA, 2025)
The development of digital technology has changed the way of doing business in the modern era. Micro, Small, and Medium Enterprises (MSMEs) in Sumber Rejeki Village face challenges in utilizing digital platforms to market their products. This community service activity aims to improve the ability of MSME actors to use digital marketing as a marketing strategy. The implementation method includes initial surveys, workshops, intensive mentoring, and evaluations. The results of the activity showed an 85% increase in participants' knowledge about digital marketing, 78% of participants were able to create business social media accounts, and 65% of participants succeeded in increasing online sales. This program has a positive impact on the development of local MSMEs and improving the village economy. Perkembangan teknologi digital telah mengubah cara berbisnis di era modern. Usaha Mikro, Kecil, dan Menengah (UMKM) di Desa Sumber Rejeki menghadapi tantangan dalam memanfaatkan platform digital untuk memasarkan produk. Kegiatan pengabdian masyarakat ini bertujuan untuk meningkatkan kemampuan pelaku UMKM dalam menggunakan digital marketing sebagai strategi pemasaran. Metode pelaksanaan meliputi survei awal, workshop, pendampingan intensif, dan evaluasi. Hasil kegiatan menunjukkan peningkatan pengetahuan peserta sebesar 85% tentang digital marketing, 78% peserta mampu membuat akun media sosial bisnis, dan 65% peserta berhasil meningkatkan penjualan online. Program ini memberikan dampak positif terhadap pengembangan UMKM lokal dan peningkatan perekonomian desa.